Influence of heat treatment on impact, hardness and fatigue strength of 6061 aluminium alloy - Nasir, Nurulhilmi Zaiedah; Mohd Daud, Mohd Ahadlin; Bapokutty, Omar; Din, Abdul Talib; Selamat, Mohd Zulkefli (Trans Tech Publications, 2015)
This paper studies the effects of various heat treatments on toughness, hardness and fatigue strength of aluminum alloy 6061. The alloy specimens were heat treated in the furnace at different high temperatures and holding times; and then cooled in different media (water and oil). Furthermore, the water quenched specimens were age hardened at 160 °C for one, three and five hours in a furnace before subsequently cooled in air. The mechanical properties such as hardness, impact and fatigue were examined. Result shows that increasing annealing as well as ageing time, increases the impact strength while decreases the hardness of the 6061 alloy. After 4 hours of annealing, the aluminum alloy showed almost 11% increase in the impact strength. The value was further increased up to 41% increase upon 5 hours of ageing at 160 °C after the quenching process.